E-Modul Puisi Berbasis Aplikasi Desia untuk Siswa Kelas X SMA - Astria Prameswari; Roekhan Roekhan; Didin Widyartono (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This research development has the goal of producing poetry e-modul and DESIA, describing the appropriateness, and the effectiveness of e-modul. This development follows the phases of ASSURE such as analyze learner characteristics, state performance objective, select methods, media, and materials, utilize materials, requires learners’ participants, evaluate and revise. The experiment carried out in control as well as experiment group to create poetry e-modul with DESIA basis, the acquired score of targeted teaching and learning activities proven to be successfully passed and effectively to be used in the activities of teaching for tenth grade Senior high school students. This e-modul has been positively accepted by the students and the Indonesian Language teachers.Abstrak: Penelitian pengembangan ini bertujuan untuk menghasilkan e-modul puisi berbasis aplikasi DESIA, mendeskripsikan kelayakan e-modul, dan mendeskripsikan tingkat efektivitasnya. Model pengembangan yang digunakan adalah ASSURE. Uji coba dengan desain kuasi eksperimen di kelas kontrol dan kelas eksperimen menghasilkan e-modul puisi berbasis DESIA, skor kelayakan bahan ajar dengan kategori sangat layak, dan bahan ajar terbukti efektif untuk diaplikasikan pada pembelajaran puisi bagi siswa kelas X. E-modul ini juga direspon positif oleh siswa dan guru bahasa Indonesia.